PENGARUH IMD DENGAN PERDARAHAN IBU 2 JAM POST PARTUM DI KOTA SEMARANG - Pawestri -; Nikmatul Khayati (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
The problem of postpartum hemorrhage needs to be a serious handling one of them with the increase of hormone oxytocin which has an important role in stimulating uterine smooth muscle contraction so that bleeding can be handled. Oxytocin hormone can be stimulated through Early Breastfeeding Iniaiation (IMD) because early initiation of breastfeeding is one of the factors affecting uterine involution where breastfeedingoccurs stimulation and release of hormones such as oxytocin hormone which causes contraction and retraction of uterine muscle. This will suppress the blood vessels resulting in decreased blood supply to the uterus. This process helps to reduce the site or place of placental implantation and reduce bleeding. The purpose of this study was to determine the effect of IMD on the number of maternal bleeding 2 hours postpartum DiKota Semarang. This type of research is and observational study using a prospective cohort design where this study compares the effects of exposed groups and the effects of unexposed groups. The sample in this study were 90 post partum mothers. Data processing is done by computerization. The data are presented in the form of frequency distribution and then tested by independent t-test, correlation and regression test to determine the effect of the relationship between the two variables. Result of research Amount of mother bleeding 2 hour post partum done initiation feeding Early average 87,20 ml with standarddevias 17,617. Number of 2-postpartum maternal bleeding not initiated 143 ml early initiation with standard deviation of 33.86. The statistical test results showed that there was an effect of IMD with 2 hours post partum bleeding with (p <0,00). There was a significant difference between the number of maternal bleeding 2 hours posr partum performed IMD action with the amount of mother's mother 2 hours post partum that is not done IMD. Efforts to reduce maternal mortality due to post partum hemorrhage by doing IMD ditatanan health services that help childbirth.Keywords: Early Breastfeeding Initiation, Labor, Bleeding